The Difference of Visual Field Defect on Diabetic Retinopathy Patients Treated with Panretinal Laser Photocoagulation with 20-Milisecond and 100-Milisecond Duration - Nova Herdana; AK Ansyori; Ramzi Amin; Irsan Saleh (Indonesian Vitreoretinal Society, 2018)
Introduction: Panretinal laser photocoagulation (PRP) is a standard treatment for severe nonproliferative and proliferative diabetic retinopathy. Twenty-milisecond duration PRP show same effectiveness with 100-ms standard PRP in inhibit neovascularization progression. This shorter pulse tend to minimize retinal neuronal defect and visual field defect. This study aim to analyze the difference of visual field defect in diabetic retinopathy (DR) patients treated with 20-ms PRP compared with 100-ms PRP in Moh. Hoesin Hospital Palembang. Methods: A clinical trial with single blinding on severe-very severe NPDR and early PDR eyes treated with PRP between June and August 2016. Forty eyes (25 patients) were randomized into two groups. Twenty eyes were treated with 20-ms PRP, and other 20 eyes treated with 100-ms PRP. Visual field defect was evaluated using Humphrey Field Analyzer 30-2 SITA Standard at baseline and 2 weeks follow-up. Result: Unpaired t-test showed significant difference in mean deviation (MD) after laser on NPDR eyes (p=0.042, p<0.05), meanwhile there was no significant difference in early PDR eyes (p=0.17, p>0.05). In NPDR eyes, more MD improvement was found in 20-ms PRP group (0.79±0.93 dB) than in 100-ms group (-0.04±0.61 dB). In early PDR eyes, MD improvement was bigger (1.0±0.88 dB) in 20-ms PRP group than in 100-ms group (0.10±1.47 dB). There was no significant difference in pattern standard deviation (PSD) on both group at any DR grade (p=0.208; p=0.201; p>0.05). Conclusion: After 2 weeks, 20-ms PRP caused more improvement and lesser visual field defect (p=0.042, p<0.05) on NPDR eyes. There was no significant difference in PSD on both groups.